Effects of Paliperidone Palmitate on Coagulation: An Experimental Study. (9th February 2014) - Yılmaz, Enver Demirel; Motor, Sedat; Sefil, Fatih; Pınar, Neslihan; Kokacya, Hanifi; Kisa, Mustafa; Oktar, Suleyman
Abstract : Objective . The aim of the present study was to examine the effects of a new antipsychotic drug paliperidone palmitate on hemogram and coagulation parameters in rats. Materials and Methods . Experiments were performed on 22 female albino Wistar rats (8–12 weeks old). Control group was given drinking water as vehicle (0.3 mL). PAL-1 rats were given 1 mg/kg paliperidone palmitate (in 0.3 mL drinking water) by oral gavage once a day for ten days and PAL-3 rats received 3 mg/kg paliperidone palmitate (in 0.3 mL drinking water) by oral gavage for ten days. Blood samples were drawn from the heart 24 hours after the last drug dose, and hemogram and coagulation parameters were measured with automated analyzers. Results . Hemogram did not change in the paliperidone treated groups compared to the controls. Factor VIII levels decreased in the PAL-1 and PAL-3 groups; and this decrease was significantly greater in the PAL-3. Factor IX levels decreased in PAL-3 rats, but its levels also increased in PAL-1 rats compared to the control. Discussion . Paliperidone has led to changes in the serum levels of coagulation factors VIII and IX in rats. As a result, paliperidone may be causing thromboembolism or bleeding in a dose-independent manner.